The Burden of Comorbid Depression and Type 2 Diabetes: An Empirical Study Using Commercial Insurance Data - SangNam Ahn; Gang Han; McKenzie Beck; Wan-Ling Hsu; Samuel D. Towne; Matthew Lee Smith; Marcia G. Ory (Journal of Primary Care & Community Health)
Introduction: Despite rising rates of depression and diabetes, assessments of depression’s burden on diabetes management and its economic burden remain limited. In this study, we evaluate the burden of depression on diabetes management and quantify the financial implications of comorbid depression and diabetes. Methods: We performed propensity score matching on Texas commercial claims data (2016-2019) to match type 2 diabetes patients with depression (n = 613) to those without (n = 583). Depression flagged in 2016/2017 indicated initial depression, and an A1C level of ≥8% in 2018/2019 indicated follow-up uncontrolled diabetes. Healthcare costs included total, diabetes-related, outpatient, and inpatient costs incurred during 2018/2019. Results: A depression flag in the initial period was linked to a 2.7 percentage point increase ( P  = .031) in the probability of having an A1C level of ≥8% in the follow-up, compared to individuals without a depression flag. Having both a depression flag and uncontrolled A1C in the initial period was associated with $2,037 higher total medical costs ( P  = .004), $494 higher diabetes-related costs ( P  = .020), and $336 higher outpatient costs ( P  = .008) in the follow-up, compared to the respective averages of $6,900, $474, and $583 for individuals without a depression flag or uncontrolled A1C. Conclusions: Our findings highlight the detrimental effect of depression on uncontrolled diabetes and the subsequent increase in healthcare costs. Further research is warranted to determine the effectiveness of proactive treatments for depression in managing diabetes, improving glycemic control, and reducing healthcare costs.